2018
DOI: 10.4314/nvj.v39i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous circulation and mutation at the hypervariable region of the VP2 gene of very virulent infectious bursal disease virus in Nigeria

Abstract: Infectious bursal disease (IBD) is a highly contagious viral disease of poultry with huge economic consequences. First reported in Nigeria in 1973, the disease has since become endemic across the country. Inspite of routine vaccine administration, outbreaks are frequently reported in vaccinated flocks which questions the effectiveness of the vaccine to confer adequate protection against the circulating strains of the virus. In this study, suspected IBD outbreaks from 9 poultry farms spanning 2015-2016 were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Based on the hypervariable region of the VP2, all four IBDV belong to the very virulent strains. Previous molecular studies on IBDV in Nigeria reported the presence of the vvIBDV strains circulating in poultry [20][21][22][23][24][25][26]. Using the criteria for classifying IBD viruses proposed by Michel and Jackwood [17], Nigerian viruses clustered with the G3 group of IBDV.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on the hypervariable region of the VP2, all four IBDV belong to the very virulent strains. Previous molecular studies on IBDV in Nigeria reported the presence of the vvIBDV strains circulating in poultry [20][21][22][23][24][25][26]. Using the criteria for classifying IBD viruses proposed by Michel and Jackwood [17], Nigerian viruses clustered with the G3 group of IBDV.…”
Section: Discussionmentioning
confidence: 96%
“…The bF was processed into 20% (w/v) homogenate as previously described [25]. The supernatant was analyzed using the agar gel precipitin test (AGPT) alongside standard IBDV antigen and antiserum (Charles Rivers, USA).…”
Section: Ibd Virus Antigen Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of acute IBD outbreaks in both vaccinated and unvaccinated chickens in Nigeria (Ojo et al, 1973;Onunkwo et al, 1975;Uzoukwu, 1981, 1982;Okoye, 1984;Durojaiye et al, 1984, 85;Abdu, 1986Abdu, , 1988Nwosuh et al, 1989; (Igbokwe et al, 2012;Shekaro and Josiah, 2015), improper vaccination at inappropriate age (Abdu, 1986;Bosha and Nongo, 2012;Igbokwe et al, 2020), lack of booster vaccinations (Igbokwe et al, 1996), IBD vaccine or immunization failures (Abdu, 1986), reversion of vaccine virus to virulence (Adamu et al, 2013) and mismatch of vaccine virus with circulating eld virus strain (Ekiri et al, 2021). The phylogenetic analyses of the Nigerian IBDV eld strains revealed a unique cluster related to imported classical and very velogenic IBD virus (vvIBDV) strains (Adamu et al, 2013) and other stains without foreign lineage that are reassortant IBD viruses (Arowolo et al, 2021) showing mutations at the hypervariable regions of VP2 gene (Nwagbo et al, 2018;Arowolo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…with subsequent positive laboratory diagnosis by molecular techniques in several reported clinical outbreaks; and the BF of chickens showing typical gross lesions yielded amplicons of IBDV in 100% of clinical outbreaks(Owolodun et al, 2015;Nwagbo et al, 2018;Arowolo et al, 2021;Omer et al, 2022).When the BF from a tentative clinical outbreak was not positive for IBDV in molecular diagnosis, it was presumed that the molecular technique was not sensitive to amplify the virus genome because of genomic mutation, reassortment and recombinations of the eld virus strain(Mwenda et al, 2018). Acute IBD is the only known disease of chickens that causes grossly visible acute exudative in ammatory swelling of the BF with hemorrhage.…”
mentioning
confidence: 99%